2017
DOI: 10.1016/j.jtcvs.2017.05.053
|View full text |Cite
|
Sign up to set email alerts
|

Methylene blue–induced serotonin syndrome after left ventricular assist device implantation: A case report and literature review

Abstract: Video clip is available online. Serotonin syndrome is a life-threatening condition of serotonin excess in the central nervous system. We report the first case to occur after a routine left ventricular assist device (LVAD) implantation. Through a systematic review of the literature, we then describe the characteristics of all previous patients with serotonin syndrome after cardiovascular procedures and identify common threads that elucidate serotonin syndrome's recent emergence. CASE PRESENTATION A 60-year-old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Serotonin syndrome following administration of methylene blue for vasoplegia after cardiac surgery has been described before. 10-12…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin syndrome following administration of methylene blue for vasoplegia after cardiac surgery has been described before. 10-12…”
Section: Discussionmentioning
confidence: 99%
“…selective serotonin reuptake inhibitors (SSRIs), MB can precipitate serotonergic excess or serotonin syndrome. 37 MB could not be used as a stand-alone remedy. Vasopressor is still mandatory to ensure the patient's survival.…”
Section: Mortalitymentioning
confidence: 99%
“…A meta-analysis in 2006 revealed that 38% of patients with New York Heart Association (NYHA) class III heart failure symptoms and 42% of those with class IV symptoms suffer from depression [3]. Recent reports have described cases of serotonin syndrome following perioperative vasoplegia in cardiac surgical patients on antidepressant medications [4][5][6]. Vasoplegia is defined by profound hypotension with normal or increased cardiac output and is a common complication of cardiopulmonary bypass, occurring in an estimated 8-10% of patients [7].…”
Section: Introductionmentioning
confidence: 99%